Prednisolone and chlorambucil therapy for idiopathic membranous nephropathy with progressive renal failure - Warwick, G L; Geddes, C G; Boulton-Jones, J M (Quarterly journal of medicine, 1994)
Twenty-one patients with membranous nephropathy, heavy proteinuria and progressive renal failure were treated with alternating monthly cycles of corticosteroids and chlorambucil for six months. Four patients received repeat courses. After a median period of follow-up of 39 months, three patients had died, six were receiving renal replacement therapy or had serum creatinine > 500 mumol/l, and one had progressive renal failure. Eleven patients had either stable or improved renal function, as judged by serum creatinine concentration. Of these eleven, four patients were in partial remission (daily protein excretion 0.2-2.0 g), and two were in complete remission. There was a tendency for those who received intravenous methylprednisolone to have a more favourable outcome. There was a high incidence of side-effects, with significant complications related to drug therapy observed in > 50% of subjects. Although individual patients appeared to respond well, sometimes dramatically, these results are less encouraging than other reports. We would urge caution in the use of this form of therapy, particularly in older patients who may have occult neoplasms, impaired glucose intolerance or pre-existing cardiac disease.